CONSTRUCTING IRAN IN THE GUARDIAN: A CRITICAL DISCOURSE ANALYSIS - Muhammad Yazir; Firma Pradesta Amanah; Yentri Anggeraini; Faiza Naurah (Jurnal Ilmiah Bina Bahasa, 2026)
This study examines how Iran is represented in a The Guardian news article that discusses post-ceasefire Iran–United States relations. The focus is placed on how media language, while appearing neutral, can still carry ideological meanings through subtle linguistic choices. The study draws on Critical Discourse Analysis (CDA), supported by Systemic Functional Linguistics and pragmatic analysis, to examine ten selected excerpts. These excerpts contain features such as modality, nominalization, negation, hedging, and rhetorical questioning, which are used to shape how Iran is linguistically constructed in the text. The analysis suggests that Iran is represented as a state actor with strategic positioning and resilience. This representation is not stated directly but emerges through repeated patterns of wording and grammatical choices across the text. In this way, language contributes to how geopolitical actors are understood in relation to power, legitimacy, and conflict. Rather than treating the news text as purely objective reporting, this study highlights how micro-linguistic patterns contribute to the framing of geopolitical actors in news discourse. However, the findings are limited to a single article and are not intended to represent Western media in general.